2015
DOI: 10.1002/mus.24659
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in amyotrophic lateral sclerosis patients and caregivers: Impact of assistive communication from early stages

Abstract: Early intervention with an ACD seems to have a positive impact on QoL and gives patients the opportunity to improve skills for communication in later disease stages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 35 publications
1
43
0
6
Order By: Relevance
“…The use of ETCS and brain–computer interfaces might facilitate psychological adaption and is likely to become more prevalent in the future . Patients with communicative disabilities should be provided with ETCS in a timely manner, as use of this technology can significantly improve QoL and reduce caregiver burden, and has the potential to alter end‐of‐life decisions . In summary, our study clearly shows the necessity of a direct and independent evaluation of LIS patients’ attitudes toward life‐prolonging measures and the need for specialized psychosocial support for NOK.…”
Section: Discussionmentioning
confidence: 80%
“…The use of ETCS and brain–computer interfaces might facilitate psychological adaption and is likely to become more prevalent in the future . Patients with communicative disabilities should be provided with ETCS in a timely manner, as use of this technology can significantly improve QoL and reduce caregiver burden, and has the potential to alter end‐of‐life decisions . In summary, our study clearly shows the necessity of a direct and independent evaluation of LIS patients’ attitudes toward life‐prolonging measures and the need for specialized psychosocial support for NOK.…”
Section: Discussionmentioning
confidence: 80%
“…In addition, a recent study found that early intervention with an assistive communication device seems to have a positive impact on QOL and gives patients the opportunity to improve skills for communication in later disease stages (Londral et al . ). However, these assistive communication devices are usually too expensive for ALS family, which may increase the burdens of ALS patients and their caregivers.…”
Section: Discussionmentioning
confidence: 97%
“…Loss of communication affects ALS patients’ ability to socialize and imposes a significant burden to the individuals QOL(41,42). Early intervention by speech therapists and use of communication devices has been shown to have a positive impact on QOL in ALS patients(41,43) and provides the patients opportunity to improve the skills for later stages of the disease.…”
Section: Discussionmentioning
confidence: 99%